Next Generation Arithmetic 4th International Conference, CoNGA 2023, Singapore, March 1-2, 2023, Proceedings - Gustafson, John.; Leong, Siew Hoon.; Michalewicz, Marek (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 4th International Conference on Next Generation Arithmetic, CoNGA 2023, held in Singapore, during March 1-2, 2023. The 11 full papers in this book were carefully reviewed and selected from 16 submissions. They were organized in topical sections as follows: Lossless FFTs Using Posit Arithmetic, PLAUs: Posit Logarithmic Approximate Units to Implement Low-Cost Operations with Real Numbers.
Lossless FFTs Using Posit Arithmetic -- Bedot: Bit Efficient Dot Product for Deep Generative Models -- A paradigm for interval-aware programming -- Decoding-free Two-Input Arithmetic for Low-Precision Real Numbers -- Hybrid SORN Hardware Accelerator for Support Vector Machines -- PHAc: Posit Hardware Accelerator for Efficient Arithmetic Logic Operations -- Fused Three-Input SORN Arithmetic -- Towards a Better 16-Bit Number Representation for Training Neural Networks -- Improving the Stability of Kalman Filters with Posit arithmetic -- Evaluation of the use of Low Precision Floating-Point Arithmetic for Applications in Radio Astronomy -- PLAUs: Posit Logarithmic Approximate Units to Implement Low-Cost Operations with Real Numbers.
Keywords: Computer arithmetic and logic units; Arithmetic and Logic Structures